Analysis of the nuclear potential for heavy-ion systems through large-angle quasi-elastic scattering - Mohd Lukman, Inche Ibrahim (2012)
The knowledge of the nuclear potential between two colliding nuclei is a fundamental ingredient in understanding a nucleus-nucleus collision. In order to study the nuclear potential, the colliding nuclei must be brought together close enough so that they experience the nuclear interaction. It has been demonstrated that large-angle quasi-elastic scattering is a suitable method to study the nuclear potential. In this thesis, analyses on the nuclear potential for heavyion systems, namely 48Ti, 54Cr, 56Fe, 64Ni, and 70Zn + 208Pb systems, have been performed through large-angle quasi-elastic scattering. At energies around the Coulomb barrier height, it has been well known that the effect of channel couplings, that is the coupling between the relative motion of the colliding nuclei and their intrinsic motions as well as transfer processes, plays an important role. Therefore, a coupled-channels procedure must be applied to take account of this effect. cqel, which is a modified version of a computer code ccfull, has been employed in order to perform these complex calculations. The nuclear potential is assumed to have a Woods-Saxon form, which is characterized by the surface diffuseness parameter, the potential depth, and the radius parameter. It is found that low values of the diffuseness parameter in comparison with the widely accepted value of around 0.63 fm are required in order to fit the experimental data at deep sub-barrier energies, that is at energies well below the Coulomb barrier height. In order to see the effect of collision energies on the deduced values of the diffuseness parameter, experimental data with energies up to 3 MeV below the Coulomb barrier height are used in the fittings. This leads to higher deduced values of the diffuseness parameter, which are closer to the widely accepted value. It seems that the phenomenon of threshold anomaly might explain the relatively low diffuseness parameters obtained at deep sub-barrier energies, and also the increase in the diffuseness parameters as the collision energies increase. It is also possible that the increase in the diffuseness parameters with respect to the energies is due to the same reasons that might cause the diffuseness parameters obtained through fusion experimental data higher than those obtained through scattering experimental data. One of the possible reasons is the dynamical effects, particularly regarding the neutron movements. Furthermore, the increase in the diffuseness parameters as the collision energies are increased also seems to have a possible tendency to be a function of the charge product of the target and projectile nuclei.